2010
DOI: 10.1530/eje-09-0919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term continuous positive airway pressure on body composition and IGF1

Abstract: Objective: To investigate the long-term effects of nasal continuous positive airway pressure (CPAP) ventilation in patients with obstructive sleep apnea syndrome (OSAS) on body composition (BC) and IGF1. Design: Observational study. Subjects: Seventy-eight (11 females and 67 males) OSAS patients who were compliant with CPAP (age 51G1.1 years) participated in the study. We assessed body mass index (BMI), total body mass (TBM), total body fat (TBF; kg) and lean body mass (LBM; kg), abdominal subcutaneous (SC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 71 publications
5
40
0
12
Order By: Relevance
“…Two studies showed that CPAP can reduce the amount of visceral fat [7,8]. However, our negative findings are in agreement with two previous studies [4,9]. A possible explanation could be that, in our study, either the duration (2 months) was too short for a significant effect to be observed or that the study did not have enough power to detect such a difference.…”
Section: Sleep-related Disorders I Kritikou Et Alsupporting
confidence: 88%
See 2 more Smart Citations
“…Two studies showed that CPAP can reduce the amount of visceral fat [7,8]. However, our negative findings are in agreement with two previous studies [4,9]. A possible explanation could be that, in our study, either the duration (2 months) was too short for a significant effect to be observed or that the study did not have enough power to detect such a difference.…”
Section: Sleep-related Disorders I Kritikou Et Alsupporting
confidence: 88%
“…A possible explanation could be that, in our study, either the duration (2 months) was too short for a significant effect to be observed or that the study did not have enough power to detect such a difference. Nonetheless, MÜ NZER et al [9], whose total study sample size was similar to ours, also did not find a significant difference, even after an 8-month CPAP treatment period. Consistent with our findings, two studies reported no improvement in weight in a clinical sample of males and females treated with CPAP after a 1-yr follow-up [29,30].…”
Section: Sleep-related Disorders I Kritikou Et Alsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present study, although our patients maintained a stable body weight throughout the trial, there was no accompanying change in visceral fat with CPAP use relative to sham CPAP. In contrast to the studies with positive findings, a more recent nonrandomised observational study by MUNZER et al [9] failed to demonstrate a reduction in subcutaneous or visceral fat after 8 months of CPAP use, where compliance with CPAP averaged 6 h per night. Similar results were also shown in an observational study by VGONTZAS et al [10] in which OSA patients were treated with nasal CPAP for 3 months.…”
Section: Discussionmentioning
confidence: 81%
“…Some observational studies have shown a reduction [7,8] while others showed no change [3,9,10]. Factors that could contribute to the differences observed include mean CPAP compliance, duration of treatment and OSA severity.…”
mentioning
confidence: 93%